A Study on the Application of MVDC Technology to Expand the Hosting Capacity of Renewable Generation in Distribution System. Issue 4 (2019) - Lee, Hansang; Jang, Gilsoo
Abstract: The changes in the distribution system that will be brought about by the expansion of renewable energy sources are expected to be unacceptable only by the existing distribution system topology. Therefore, in order to realize the quantitative expansion based on the qualitative improvement of technology, this paper proposes combination of the planned solution to convert AC D/L to DC D/L and the operational solution to convert NOP to SOP.